study of the relationship between the pain on the place of scar in women with previous cesarean section and scar opening during cesarean section - احسان, علا; رمضان, لينا; محمد, باسل (Latakia University Journal -Medical Sciences Series, 2022)
Objective: The main objective of this study is to early detection the cases of opening the scar and its relationship with the pain on scar. The secondary objective: 1-reduce the rate of the cesareans in patients with one previous cesarean section(LSCS). 2-reduce the complications rates of recurrent cesareans. Patients and methods : A case-control study was conducted at Tishreen University Hospital in Lattakia from 1st February 2021 to 1st February 2022. 232 pregnant women who had one transverse cesarean section were included in the study. Incidence of uterine rupture was compared between women who underwent repeated cesareans owing to uterine scar tenderness (study group) and women who underwent repeated cesareans without uterine scar tenderness(control group). Results: The current study showed that the incidence of uterine rupture was1.05 % in the study group and 1.46 % in the control group. but the incidence of scar rupture was7.37 % in the study group and 5.84% in the control group. Data were examined using chi-square test (p-value 0.05 with confidence interval 95%) In our study we fined that p-value > 0.05 that means there was no difference in incidence of uterine rupture between the groups with confidence interval 95%. Sensitivity of the pain as an indicator of uterine rupture was 32.48% ,specitivity 66.09 %, positive predictive value was 8.42%,and negative predictive value was 91.58 % . As a result, sensitivity and specitivity of uterine scar tenderness as an indicator of uterine rupture were low, but the negative predictive value was high. Conclusion: Isolated scar tenderness in women with previous cesarean is a poor indicator of uterine rupture.